Planning for cycling : principles, practice, and solutions for urban planners - McClintock, Hugh (Woodhead Publishing in environmental management., 2002)
Creating an effective policy for cycling is now an essential part of developing a sustainable transport strategy for both local and national governments. There is now a wealth of international experience of how well cycling planning works in practice and how it can be improved. With a wide range of contributions from America, Australia and Europe, Planning for cycling sums up many of the lessons learnt and shows how they can be applied in improving urban planning.